Politics of HIV Vaccine Research from International to Global Health - David, Pierre-Marie (Anthropologica, 2024)
Paradoxically, the absence of HIV vaccine has been very structuring for global vaccine logics, and, more broadly, “global health” research. HIV vaccine research has oscillated between optimism and pessimism and has been central to the humanist justification for research in the South. From the attempt by the World Health Organization’s Vaccine Development Unit (VAD) on AIDS to become the centre of an “international” coordination effort to the diplomatic work involved with Thailand’s HIV research, I describe political contexts, and postcolonial power relations connected to HIV vaccine research. I argue that the failure of “international” coordination has paved the way for another politicization of global HIV vaccine research which led to a shift away from inter-state diplomacy to a “stateless” situation where the global vaccine logics contribute to the development of an experimental regime that relies on the capture of public resources and the availability of depoliticized biological subjects for the purposes of private valorization.